IMPLANTS FOR EXTRACAPSULAR NECK OF FEMUR FRACTURE DYNAMIC HIP SCREW VERSUS INTRAMEDULLARY NAILING - Butt, Faisal Farooq; Hussain, Adnan Shabbair; Khan, Ahmed Mushtaq; Sharif, Maria (Journal of Ayub Medical College Abbottabad, 2017)
Neck of femur fractures are the most prevalent type of injury in elderly trauma patients. Both intra and extra capsular type of fractures are equally distributed in the given population. Traditionally, Extra capsular fractures are fixed with Dynamic Hip screw or Intra medullary nailing based on the type of fracture. NICE (National institute of clinical excellence) recommends fixing 31-A1 and 31-A2 fractures with DHS (Dynamic Hip Screw) whereas AO recommends fixing 31-A1 with DHS and 31-A2.1 subtype with DHS and 31-A2.2 and 31-A2.3with IMN (Intra medullary nail). In regional trauma centre 178 patients, 125 females and 53 males with extra capsular neck of femur fractures fixed were selected in a retrospective study. The data was spanning over a period of 1 year. Fractures were classified as per AO classification by two registrars. The implant selection was analysed in terms of the short term out come to find out the cost effectiveness of one over the other. The quality of reduction was assessed as per standard criteria and consideration of lateral femoral wall thickness was taken into account to assess the stability of fracture. The study found more risk of peri prosthetic fractures associated with Intra medullary nailing as compared to Dynamic Hip screw and more risk of Varus collapse was found to be associated with DHS as compared to IM Nail. Moreover, despite of Nail being costly as compared to DHS, the study did not reveal its superiority in terms of inpatient hospital stay. In appropriately selected patient DHS provides results in terms of hospital stay, revision rate and wound complications comparable to IM Nail in the short term justifying its use in the above-mentioned fracture patterns as per the standard National Institute of clinical Excellence guidelines. Keywords: femur fractures; screw; Intramedullary nailing; trauma centre; acetabulum